Data managers' perspectives on OAIS designated communities and the FAIR principles: mediation, tools and conceptual models. Issue 6 (3rd June 2020) - Donaldson, Devan Ray; Zegler-Poleska, Ewa; Yarmey, Lynn
Abstract : Purpose: This paper presents results of a study on data managers' perspectives on the evolution of Designated Communities and the FAIR Principles using an example of a geological repository. Design/methodology/approach: The study employed 10 semi-structured interviews with data managers at a state geological survey and qualitative analysis of the interview transcripts. Findings: The Designated Community for a collection in this data repository has evolved from petroleum industry users to include academic researchers and the public. This change was accompanied by significant user interaction changes from in-person, reference interview-style conversations to anonymous digital, automated interactions. The main factors driving these changes were developments in technology which allowed the data managers to shift data discovery and access into the online environment. The online data portal has seen increasing non-expert use, driving the data team to develop additional services for these new communities. Repository data team participants varied in their familiarity with the FAIR Principles and their perceptions of the FAIRness of the data in the repository. Research limitations/implications: The study was limited to one organization in the United States. However, the results are applicable to other data environments working through the tensions between high-level global frameworks such as FAIR, and continuing to serve the day-to-day needs of their designated communities. Continued work on how to assess success in this complex space is needed. Originality/value: This paper lies at the nexus of two digital preservation frameworks and contributes to a limited extant literature providing guidance on implementing the concept of a Designated Community in practice.